Competency of innovative thinking of case study teachers at SMPN 10 Singkawang - Noni Noni; Indri Astuti; Afandi Afandi (Universitas Kanjuruhan Malang, 2023)
The educational process carried out must run optimally, therefore the teacher has an important role in developing and designing a lesson in order to provide a maximum learning experience for students. Innovative teacher competencies must be owned by today's teachers. This study aims to see and assess the competence of innovative teachers at SMPN 10 Singkawang. The sample in this study was 15 teachers who taught at SMPN 10 Singkawang by filling out an innovative teacher competency questionnaire. The questionnaire consists of 4 indicators, namely observing, asking questions, networking ideas, and experimenting. Innovative competency assessments are very helpful in providing an overview of the qualities possessed by teachers so that improvements can be made for the better. The quality of teachers at SMPN 10 Singkawang is clearly reflected in the results of the study, teachers at SMPN 10 Singkawang have innovative teacher competencies with good criteria. (Average: 73.03).